2012
DOI: 10.1021/pr2011878
|View full text |Cite
|
Sign up to set email alerts
|

Temporal and Spatial Profiling of Internode Elongation-Associated Protein Expression in Rapidly Growing Culms of Bamboo

Abstract: In natural conditions, culms of developing Moso bamboo, Phyllostachys heterocycla var. pubescens, reach their final height of more than ten meters within a short period of two to four months. To study this phenomenon, bamboo culm material collected from different developmental stages and internodes was analyzed. Histological observations indicated that the development of culm was dominated by cell division in the initial stages and by cell elongation in the middle and late stages. Development, maturation, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
109
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(111 citation statements)
references
References 91 publications
2
109
0
Order By: Relevance
“…A recent proteomics study showed that many metabolic processes of cell wall structure were employed in the fast growth of bamboo culms 23 npg l e t t e r s the genes that might affect the formation of the cell wall structure. We detected 19 cellulose synthase (CesA) and 38 cellulose synthase-like (Csl) genes 24,25 in the bamboo genome, representing nearly the highest copy number of these genes among the 7 sequenced plant genomes (Supplementary Table 14a).…”
Section: E T T E R Smentioning
confidence: 99%
“…A recent proteomics study showed that many metabolic processes of cell wall structure were employed in the fast growth of bamboo culms 23 npg l e t t e r s the genes that might affect the formation of the cell wall structure. We detected 19 cellulose synthase (CesA) and 38 cellulose synthase-like (Csl) genes 24,25 in the bamboo genome, representing nearly the highest copy number of these genes among the 7 sequenced plant genomes (Supplementary Table 14a).…”
Section: E T T E R Smentioning
confidence: 99%
“…With these characteristics, bamboos have been fascinating plants among researchers since long. To explore their remarkable growth characteristics, comparative histological studies, monoclonal antibody bank creation, biochemical, and proteomic profiling of various developmental stages of growing shoot of bamboos have been done (Lee and Chin, 1960; Zheng et al, 1998; Lin et al, 2002; Li et al, 2007; Wang et al, 2011; Cui et al, 2012). Candidate genes ( Sucrose synthase, Cellulose synthase, BoSUT2, BoPAL1, Invertase ) associated with growth have been characterized in Bambusa oldhamii (tropical bamboo; Chiu et al, 2006; Hsieh et al, 2006, 2011; Chen et al, 2010; Gao et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…In rice, stem internodes rapidly elongate at the beginning of the reproductive stage (Bosch et al, 2011; Slewinski, 2012). Many important biological processes including cell division, cell wall synthesis, and cell wall remodeling occur during stem development (Bosch et al, 2011; Cui et al, 2012). Among these processes, the change in cell walls is especially important for stem mechanical properties (Gritsch and Murphy, 2005; Wang et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…For example, fewer than 60% of transcripts are translated into proteins in maize (Walley et al, 2016). The current grass stem proteome data for rice, Brachypodium distachyon , sugarcane and bamboo consist of fewer than 600 proteins for a given species (Yang et al, 2006; Cui et al, 2012; Douché et al, 2013; Calderan-Rodrigues et al, 2016). Previous gel-based proteomics studies of rice stems identified fewer than 300 proteins, likely missing many proteins involved in important biological processes (Nozu et al, 2006; Yang et al, 2006).…”
Section: Introductionmentioning
confidence: 99%